Environmental conservation and psychoanalytic defense mechanisms. The case of the Cachoeira River Watershed, Joinville – SC- Brazil - Junqueira, Sandra Tireck; Prates, Rodolfo Coelho (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The present study aimed to evaluate the defense mechanisms used by residents in the surroundings of the Cachoeira River Watershed, which is severely polluted and considered the most vulnerable to degradation in the municipality of Joinville - SC. Defense mechanisms were described by Freud as unconscious processes through which the ego dissociates itself from impulses or affects that it considers threatening and that bring suffering. In relation to environmental issues, these mechanisms can act powerfully to create inconsistencies between professed attitudes and behaviors in relation to norms against environmental degradation, the culture of reducing toxic waste, climate change, etc. This is a qualitative study, in which seven residents participated, evaluated using three individual interviews. Defining the number of participants involved the snowball sampling. The interviews were audio-recorded, transcribed in full and analyzed independently. Idealization, projection, rationalization, denial, and apathy were the most frequently identified defense mechanisms in the case studies, corroborating the hypothesis of the emergence of anxiety and suffering in the face of threatening environmental situations. The conclusion of this study is that understanding the defensive functioning of people who face these situations can help to improve more effective interventions in programs and campaigns aimed at environmental conservation.